2020
DOI: 10.14639/0392-100x-n0776
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a large cohort of adult patients with Ménière’s disease: bedside and clinical history

Abstract: Objective. The purpose of this study was to assess vestibular findings and clinical history in a large cohort of patients affected by Ménière's disease. Methods. We retrospectively analysed 511 adult patients fulfilling criteria for definite unilateral Ménière's disease according to Barany Society. Thorough clinical history, audiometric exam, central nervous system MRI, quantification of serum autoantibodies and complete vestibular function test were performed. Results. Mean age at clinical record was 55.4 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
3
20
1
Order By: Relevance
“…In larger series of non-operated MD, it was demonstrated that SVIN may be observed in 59% to 66% of cases [ 24 , 25 ] and usually shows a low SPV < 4°/s (3.89 ± 3.9°/s) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In larger series of non-operated MD, it was demonstrated that SVIN may be observed in 59% to 66% of cases [ 24 , 25 ] and usually shows a low SPV < 4°/s (3.89 ± 3.9°/s) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients may experience a myriad of symptoms consisting of (but not limited to) tinnitus, aural fullness, or a sudden fall without loss of consciousness known as drop attacks (14)(15)(16). Migraine and autoimmune diseases are common comorbidities, reported in up to 16 and 11% of patients respectively (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Migraine vertigo (MV) and Ménière's disease (MD) share several signs and symptoms such as tinnitus, fullness, photophobia, phonophobia, headache and vertigo spells lasting hours 1,2 . Diagnosis of MD or MV is based on anamnes-tic data and clinical features, making differential diagnosis very difficult 3 .…”
Section: Introductionmentioning
confidence: 99%